Acute hepatitis in a young woman with systemic lupus erythematosus: a diagnostic challenge - Barosa, Rita (BMJ Publishing Group, 2013)
A 48-year-old woman with systemic lupus erythematosus diagnosis was on naproxen, hidroxichloroquine and acetylsalicylic acid. She had self-suspended all medication and resumed 1 year later. Five days after the medication was resumed, she developed acute hepatitis, with biochemical hepatic cytolysis, hypergamaglobulinaemia and a serum antinuclear antibody titre of 1/2560. Idiopathic autoimmune hepatitis was considered, but drug-induced liver injury could not definitely be ruled out. Patient declined liver biopsy. Oral prednisolone was started. Within 3 months with prednisolone being tapered to 10 mg/day, a new flare occurred. Liver biopsy was performed and it favoured autoimmune hepatitis diagnosis. We discuss the diagnostic options and treatment approach in a patient with autoimmune disease and possible drug-induced liver injury who initially declined liver biopsy.